Hubungan Pemakaian Kontrasepsi Hormonal Jenis Suntik Depo Medroxy Progesterone Acetate (Dmpa) Dengan Perubahan Berat Badan Pada Akseptor Kb Di PMB Patmawati Pinrang - Sitti Hadriyanti Hamang; Suryanti S; Nia Karuniawati (An Idea Health Journal, 2025)
Efforts to create a prosperous society and create a quality family include controlling the number of births, regulating, spacing or limiting pregnancies by participating in a family planning program. This research method uses a survey with a cross-sectional study method with a sample size of 64 respondents, then a literature review is carried out then continued with planning and data collection. Based on the Mann-Withney test, it shows a p value of 0.036, indicating that there is a relationship between the use of depo medroxy progesterone acetate injectable contraception and changes in body weight in family planning acceptors at BPM Patmawati.